Hystological Changes Of The Spleen In Experimental Rheumatoid Arthritis And Morphological Alteration After Pathogenic Treatment - Mashrab Rustamovich, Turdiyev; Guljamol Fazliddinovna, Makhmudova; Uyg’unovich, Nurboboev Adkham; Ziyoda Rakhmonovna, Sokhibova (Journal of Neonatal Surgery, 2025)
After the use of anti - inflammatory nonsteroidal agent (meloxicam) and pomegranate seed oil, regeneration processes were recorded in the structure structures of the White - breed bats, the mass of the spleen was on average-1205±7.12 mg in 18-month-old white-breed rats, and on average-1138±6.21 mg in 24-month-old white-breed rats. The diameter of the venous sinuses in the red pulp was 0.38±0.01 µm in 18-month-old rats and 0.25±0.05 µm in 24-month-old rats. The area of venous sinuses was reported to have decreased from an average of - 74,381±1.19 mkm2 in rats at 18 months compared to rats in the rheumatoid arthritis-calling group, to an average of 69,251±0.99 mkm2 in rats at 24 months. The total area of red pulp was 984-35.24±1.97 mkm2 in 18-month rats, 875-61. 19±2.01 mkm2 in 24-month rats.